Necessity of the Periodical Ultrasound Assessment of the Peripheral Venous System in Intensive Care Unit Patients. - Dagadaki, Ourania; Birbas, Konstantinos; Mariolis, Theodoros; Baltopoulos, George; Myrianthefs, Pavlos (Ultrasound Med Biol, 2019)
The utility of periodic sonographic assessment and monitoring for early diagnosis of deep vein thrombosis (DVT) in patients hospitalized in intensive care units (ICUs) was investigated. Of 314 patients hospitalized in an ICU over a 24-mo period, 248 were examined. The first examination of the patients was carried out within the first 48 h of ICU admission, and weekly examination followed until discharge. Peripheral veins were examined according to the general principles of the ultrasound study using the compression test in B-mode imaging (image to gray scale). The criterion for the absence or presence of a clot within the lumen was the presence or absence of full compressibility of the venous lumen, respectively. Intermittent compression was applied to multiple cross sections along the entire extent of the limbs. Three patients (1.2%) were diagnosed with sub-clinical DVT. The diagnoses were made on the third (sapheno-femoral junction), fourth (right internal jugular) and fifth (left gastrocnemius) weeks of hospitalization, respectively, although patients received full anticoagulation prophylaxis. DVT in a general-population ICU patient on anticoagulation prophylaxis did not seem to occur very frequently, and hence, regular ultrasound monitoring is not recommended. However, it may have value after the third week or in a selected population of ICU patients with very severe and/or multiple predisposing factors or who are not undergoing anticoagulant treatment because of contraindications.